Life history characteristics of the rove beetle, Dalotia coriaria (Coleoptera: Staphylinidae) under laboratory conditions - Echegaray, Erik R.; Cloyd, Raymond A. (My University, 2014)
Rove beetles (Coleoptera: Staphylinidae) have been reported as predators of animal and human disease vectors and of insect pests associated with field and greenhouse crops including species in the genera Aleochara, Holobus, Paederus, Dalotia, Staphylinus and Philonthus; however, there is limited information on their life history parameters. The rove beetle Dalotia coriaria (Kraatz) is a predator of greenhouse pests including fungus gnats. In this study, stage-specific and total development, fecundity, longevity, and sex ratio were investigated under laboratory conditions using growing medium as a substrate, which was designed to simulate what rove beetles would experience under greenhouse conditions. Duration of life stages was 2.2, 7.1, and 7.8 days for egg, larva and pupa respectively, whereas total development time from egg to adult was 17.0 days. Average fecundity was 90.2 eggs per female and the number of adults produced per female was 69.1. In addition, D. coriaria male and female adult longevity was 60.3 and 47.8 days. The sex ratio was 1:1 (females:males). These results will be helpful in improving augmentative biological control and mass-rearing.
Citation: Echegaray, Erik R., and Raymond A. Cloyd. 2013. “Life History Characteristics of the Rove Beetle, Dalotia Coriaria (Coleoptera: Staphylinidae) under Laboratory Conditions.” Journal of the Kansas Entomological Society 86 (2): 145–54. https://doi.org/10.2317/JKES120927.1.
Keywords: Biological control; Bioassays; Development; Longevity; Fecundity; Sex ratio